Tra il Nilo e il Ticino: la collezione egizia del Museo Archeologico dell’Università degli Studi di Pavia (Gilgameš, 2019)
The paper aims to provide a historical presentation and a briefdescription of the quite unknown manufacts kept in the Egyptiancollection of the Archaeological Museum of the University of Pavia.The materials, most of them gifts given by scholars, travellers andscientists, in the fist mid of the 19th century, are a good evidenceboth of the so-called “Egyptomania” and the beginning of theinterest in egyptologicals “studies” in Northern Italy. The reader willfind, after a historical introduction, a short overview of the materialsand a presentation of some ongoing projects for the valorizationand the fruition of the collection itself.